"Booster Days": An educational initiative to develop a community of practice of primary care collaborative memory clinics. Issue 1 (2nd January 2020) - Lee, Linda; Hillier, Loretta M.; Weston, W. Wayne
ABSTRACT: This study explores the value of a Booster Day education initiative for clinicians working in interprofessional Primary Care Collaborative Memory Clinics (PCCMC) to share updates in dementia care, challenging cases, key lessons learned, and best practices, as a mechanism to foster learning and support the PCCMC Community of Practice (CoP). Between 2010 and 2016, 17 annual Booster Days were delivered to health professionals who completed the PCCMC training program. All participants were invited to complete an evaluation survey in which they identified the ways in which the sessions have been helpful; 89% (1361/1530) completed surveys. The Booster Days were valued as opportunities for networking to learn from other clinicians, fostering a sense of community, learning new information, learning to support practice improvements, and team building. An annual Booster Day that incorporates active participant engagement, information sharing, and networking may effectively support CoPs, learning, team building, and practice change within interprofessional teams.